2022
DOI: 10.1097/iae.0000000000003612
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Lifetime Imaging Ophthalmoscopy as Predictor of Long-Term Functional Outcome in Macula-Off Rhegmatogenous Retinal Detachment

Abstract: Macular fluorescence lifetimes 1 month after the surgery for macula-off rhegmatogenous retinal detachment correlate significantly with long-term functional outcomes at 6 months after the surgery

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
(66 reference statements)
0
2
0
Order By: Relevance
“…MP analysis with digital filters represents another biomarker that can be measured intraoperatively, potentially serving as a predictive factor for postoperative outcome in macular diseases. Jaggi et al recently demonstrated that postoperative MP fluorescence was predictive of long-term postoperative outcome in cases of retinal detachment [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…MP analysis with digital filters represents another biomarker that can be measured intraoperatively, potentially serving as a predictive factor for postoperative outcome in macular diseases. Jaggi et al recently demonstrated that postoperative MP fluorescence was predictive of long-term postoperative outcome in cases of retinal detachment [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical fluorescence lifetime ophthalmoscopy (FLIO; Heidelberg Spectralis, Heidelberg, Germany) measures FL simultaneously with FAF over the central 30 degrees of the retina. Clinical FLIO has shown changes in clinically normal retina 11 and many retinal diseases 12 , 13 including AMD. 11 , 14 Adaptive optics fluorescence lifetime ophthalmoscopy (AOFLIO) provides finer axial resolution (approximately 40 microns) than standard clinical FLIO techniques.…”
mentioning
confidence: 99%